Prevailing Motifs in the Meranaw Rina-Rinaw: A Thematic Study - Hasmina Sarip (RIRAI Publisher, 2024)
This study aims to uncover the prevailing motifs in the Meranaw rina-rinaw texts and. Through thematic analysis, this study determines how faithful the rina-rinaw has remained to the prototype, the traditional bayok, or how far it has drifted from the latter. Specifically, this study seeks to identify different motifs dominating the texts. The findings revealed that the rina-rinaw texts employ a rich variety of motifs or recurring themes which are the essential stuff of which songs are made to draw traction and engage the listeners. They enliven the experience or world portrayed in the songs. Most importantly, this study poses a challenge to future researchers to attempt forays into other aspects of the Meranaw culture. This study on the rina-rinaw, as one of the many “undocumented” Meranaw art forms, provides only a foretaste of much more that the unique and rich Meranaw cultural heritage has to offer.